Distributed Control of Mobile Sensor Networks under RF Connectivity Constraints. (8th June 2012) - Stergiopoulos, Yiannis; Kantaros, Yiannis; Tzes, Anthony
Abstract : This paper addresses the problem of coordinating the motion of the nodes in a mobile sensor network for area coverage applications under RF communication limitations. During network evolution, the area sensed by the network increases until it reaches optimum configuration, while information for decision making is acquired distributively among the nodes via a prespecified number of hops. Unlike previous works, radio range is not demanded to be at least twice the sensing range, imposing an extra constraint in the overall problem setup. The proposed control scheme guarantees end-to-end RF connectivity of the network, while attaining optimum area coverage. Results are further verified via simulation studies.